Management of Counseling Guidance in Handling Student’s Delinquency in Madrasah - Jarkawi, Jarkawi; Madihah, Husnul (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study aims to understand the management of counseling guidance in dealing with student delinquency in MTs Negeri 1 Banjarmasin City. Of the many student delinquency behaviors that occur at MTs Negeri 1 Banjarmasin City, the triggering factor is dominated by the influence of close friends, environment, and existence in the eyes of their friends. This study uses a qualitative case study type method. The data collection technique was carried out through interviews with the head of the madrasa, deputy head of the madrasa, counseling teachers and students, observation, and documentation. The data analysis is carried out in stages, starting from data presentation, data reduction, and concluding. The results showed that the planning of counseling guidance was based on the needs of students, parents, and madrasas, which was carried out systematically. Meanwhile, the implementation is carried out by referring to the standards set by the madrasa. The evaluation is carried out regularly every month, semester, and yearly to determine the extent of the success and obstacles of the guidance program. Through planned and systematic counseling, students will have a good and superior personality.